Clinicopathologic Features and Prognosis of Duodenal Adenocarcinoma and Comparison with Ampullary and Pancreatic Ductal Adenocarcinoma - Zenali, Maryam (Hum Pathol, 2013)
Due to the rarity of duodenal adenocarcinoma (DAC), the clinicopathologic features and prognostication data for DAC are limited. There are no published studies directly comparing the prognosis of DAC to ampullary adenocarcinoma (AA) and pancreatic ductal adenocarcinoma (PDA) after resection. In this study, we examined the clinicopathologic features of 68 patients with DAC, 92 patients with AA and 126 patients with PDA, who underwent resection. Patient clinicopathologic and survival information were extracted from medical records. Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) with two-sided significance level of 0.05. Patients with DAC had higher American Joint Committee on Cancer (AJCC) stage than AA patients (P=0.001). Lymph node metastasis (P=0.013) and AJCC stage (P=0.02) correlated with overall survival in DAC patients. Patients with DAC or AA had lower frequencies of lymph node metastasis and positive margin and better survival than those with PDA (P<0.05). However, no differences in nodal metastasis, margin status or survival were observed between DAC patients and those with AA. Our study showed that lymph node metastasis and AJCC stage are important prognostic factors for overall survival in DAC patients. Patients with DAC had less frequent nodal metastasis and better prognosis than those with PDA. There was no significant difference in prognosis between DAC and AA.